1990
DOI: 10.1073/pnas.87.15.5613
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-colony-stimulating factor (CSF-1) induces proliferation, chemotaxis, and reversible monocytic differentiation in myeloid progenitor cells transfected with the human c-fms/CSF-1 receptor cDNA.

Abstract: The c-fms protooncogene encodes the receptor for macrophage-colony-stimulating factor (CSF-1). Expression vectors containing either normal or oncogenic pointmutated human c-fins genes were transfected into interleukin 3 (IL-3)-dependent 32D cells in order to determine the effects of CSF-1 signaling in this murine clonal myeloid progenitor cell line. CSF-1 was shown to trigger proliferation in association with monocytic differentiation of the 32D-c-fins cells. Monocytic differentiation was reversible upon remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 36 publications
3
57
2
Order By: Relevance
“…To avoid such abnormal conditions, cells have to be particularized in such a way as to differentiate or proliferate in response to appropriate biological stimuli. Experiments have shown that, besides other factors [58,59], the mechanical structure of cellular micro-environments plays an important role in cell differentiation and proliferation [22,23,31,67]. For instance, Mesenchymal Stem Cells (MSCs) differentiate into specific phenotypes with high sensitivity to the tissue rigidity where they reside in.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid such abnormal conditions, cells have to be particularized in such a way as to differentiate or proliferate in response to appropriate biological stimuli. Experiments have shown that, besides other factors [58,59], the mechanical structure of cellular micro-environments plays an important role in cell differentiation and proliferation [22,23,31,67]. For instance, Mesenchymal Stem Cells (MSCs) differentiate into specific phenotypes with high sensitivity to the tissue rigidity where they reside in.…”
Section: Introductionmentioning
confidence: 99%
“…PDGF receptor responded to such growth factors m the same way as eplthehal or mesenchymal cells did when stimulated by EGF or PDGF respectively [5,26] IL3, on the other hand, activated the turnover of phosphatldylcholme slnularly to the extent m a mast/megakaryocyte cell lme [21], thus substantiating the hypothesis that phosphatldylchohne turnover m response to mterleukms was a common feature of hematopoletlc cells [29] The effect of CSF-1 on slgnalhng m c--ns-expressmg cells was rather mtrigumg m fact, earher studies reported that CSF-I was not able to stimulate the 'classicdl' turnover of mositol hplds either m macrophages that endogenously express its receptor or m BALWc fibroblasts made to express the receptor [6] However, overexpression of CSF-1 receptor m 32D cells and m NM/ 3T3 fibroblasts [4] led us to observe a small, but slgnificantly reproducible, accumulation of rnosltol phosphates m response to the factor (Table I). Several explanations may account for this phenomenon The CSF-I receptor gene product shares structural and sequence slmllarlties with the PDGF receptor however, while tyrosme kmase domains are very similar, their kmase insert domains are highly unrelated both m predicted sequence and length In a recent study we demonstrated that insertion of the c-ftns kmasc insert domain could reconstitute brochemlcal and bIological respor,ses to PDGF, m 32D cells expressmg a deletion mutant of the c1 PDGF receptor lackmg the original kmase insert [9] Using a similar approach we also demonstrated that tyrosmc mutations wlthm the cx PDGF receptor kmasc insert domain could abi ogate receptorassociated phosphatldylmosltol-3 kmasc activity wlthout affectmg phosphomosltide turnover and mltogemc and chemotactlc signal transduction [30] These results support the consrderatlon that stmlulation of mosltol lipid metabohsm appears to be a mandatory event m PDGF slgnalhng [30,31] Therefore, it IS proposed that the overexpiessed c-fins product might Interact with, nnd stimulate with low efficiency, the PDGF slgnalling pathway, thus leading to mosltol phosphate formatlon Future studies will detcrmme whether the phosphoinosltldase C expressed m 32D cells 1s a good substrate for CSF-1 receptor tyrosme kinasc In addition to the hydrolysis of phosphomosltldes.…”
Section: Discussionmentioning
confidence: 99%
“…!& abl, and src[l]) or by mtroductlon of foreign growth factor receptor genes followed by stimulation with the appropriate growth factor Thus, we demonstrated that growth factors as diverse as epldelmal growth factor (EGF), platelet-derived growth facto1 (PDGF), and colony stlmulatmg factor-l (CSF-1) could sustain 32D cell prohferatlon once the receptor gene had been introduced into cells [2][3][4] Since such a vancty of growth factors and oncoprotems could lead to a slmllar feature (abrogation of IL3 requirement), we reasoned that common signal transducmg elements were activated by IL3, EGF, PDGF, CSF-I, and during oncogcne-induced transformation However, it is known that each one of these factors rehes on different signal transducing mechanisms to elicit mltogemc responses. EGF and PDGF stimulate the turnover of mosltol hplds with formation of dlacylglycerol and tnositol phosphates (for review see [5]); CSF-1 seems to activate phosphdtidylmositol-3 kmase in macrophages and fibroblasts without triggering mosltol hpld hydrolysis [G]; IL3, on the other hand, activates protcm klnuse C (PKC) without mcreasmg inositol lipid turnover [7,8] …”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the wt-p53 induced di erentiation we observed in the 32Dsrc-transformed cells was through the monocytic pathway. This was a rather surprising result since 32D cells possess the G-CSF receptor and di erentiate into granulocytes upon stimulation with G-CSF , whereas they do not express the c-fms/CSF-1 receptor for macrophage-colony stimulating factor (M-CSF) and do not normally di erentiate into monocytes/macrophages Pierce et al, 1990). Interestingly, the c-src protein belongs to the signal transduction pathway of c-fms (Courtneidge et al, 1993).…”
mentioning
confidence: 99%
“…It has been reported that transfection of 32D cells with a constitutively activated CSF-1 receptor ± the c-fms [S301,F969] ± induces IL-3-independence and tumorigenicity (Pierce et al, 1990). We wished to clarify whether p53 has a suppressive action which produces di erent Âźnal outcomes depending on the pathways activated by the transforming oncogenes.…”
mentioning
confidence: 99%